(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article analyzes the Turkic philosophy of music for the first time in two aspects: actually as a philosophy of Turkic music and as a Turkic philosophy of music. In the first aspect, the understanding of music is given in the context of the Turkic worldview and various definitions of music, the concept of «saz» specific to Turkic music is highlighted. Attention is focused on the ontology of Turkic music and its sacred, mystical meaning. The work of Korkyt Ata is used in this analysis. In the second aspect, the historical development of the Turkic philosophy of music from Al-Farabi to Darwish Ali (from the 9th to the 16th century) is analyzed. Concepts of music of Alisher Navoi and Nizami Ganjavi, Ash-Shirazi and Kawkabi were presented for the first time from the standpoint of their philosophical content.